The Factors which Influence Corn Production - Sutarni Sutarni; Marlinda Apriyani (Politeknik Negeri Lampung, 2011)
Corn is food plant which has important rule in contributing food for human and livestock. This research aims to analyse the factors which Influence Corn Production and condition economic scale of of corn farming. This research was conducted in Jatiagung subdistrict on May-September 2007. Analyse method of it used Statistic analysis method of double regression with Cobb-douglas production fuction. The result of this research indicates the factors which Influence Corn Production are length of land farming , KCL fertilizer, organic fertilizer labor and factors which do not Influence corn production are seed, urea fertilizer, TSP fertilizer and the desire of farmers take the risk of corn farming. Elasticity of corn farming in the research area is 1,17 . It means that it is increasing return to scale. It indicates that additional of production factors will cause bigger production additional. . Key Words: Production, Economic return to scale, cobb douglas, production elasticity